Measurance of Pitch Plane and Offline Detection of Accuracy on Hirth Coupling - Guangjun Shao; Jianxin Yao; Shaobo Kang; Dongfei Wang; Kai Tang; Chao Song; Jia Dong (Jixie chuandong)
The hirth coupling is widely used in the centrifugal air compressor unit due to its characteristic of high torque capacity，self centering and so on. A feasible method for the measuring of pitch plane is illustrated and the offline detection for the accuracy of hirth coupling is carried out by using gear tester， some reference for the measurement of relevant parts and the offline detection are provided.